Butoconazole and miconazole in treating vaginal candidiasis. - Bradbeer, C S (1985)
In a single blind trial, a three day course of butoconazole nitrate cream was compared with a seven day course of miconazole nitrate cream, both applied intravaginally, in treating vaginal candidiasis. They were equally effective. The cure rate for patients treated with butoconazole was 82.8% at the first follow up (a mean of 18.4 days from the beginning of the treatment) and 76.7% at second follow up (a mean of 40.4 days). Cure rates for patients treated with miconazole were 84.4% and 75.8% respectively. The differences between these cure rates were not significant.